DAMPAK PINJAMAN TERHADAP PENGEMBANGAN USAHA ANGGOTA CREDIT UNION KELING KUMANG SIANTAN - B21108007, Juali (Jurnal Pembangunan dan Pemerataan, 2015)
Title of this thesis is the study’’ Impact of Business Development Loans Against Members Credit Union Rivet Kumang Siantan’’. The problem in this study is’’ how the Impact of the Credit Union Loans Provided To Members Credit Union Rivet Kumang Siantan’’. Whereas the purpose of this study was to analyze the impact of loans granted by the Credit Union Rivet Kumang Siantan.   This study uses descriptive method, a method that a portrait of the situation and the condition for what is happening in the fieid with the primary data and secondary data. Purposive sampling with a total of 74 respondents Credit Union members worked small traders.   The results of the study most of the members Credit Union Rivet Kumang feel the real impact of the loans granted by the Credit Union Rivet Kumang Siantan, the visible impact of the increase in capital, increasing the number of types of goods, increased profitsn even though most of the workers do not grow and do not change their place of business.   Keywords : Loans and Business Development.